Penerapan Hukum terhadap Tindak Pidana Korupsi Anggaran Ternak (Studi Putusan No.1/Pid.Pra/2019.Pn.Lsm) - Ferdy Saputra; Ramaniatun Ramaniatun; Phoenna Ath Thariq; Dara Quthni Effida (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The crime of corruption is a special offense which is regulated separately in the criminal law book. In the process of handling corruption cases, the principle of priority or precedence in the settlement process applies. This is in accordance with Article 25 of Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, which states that investigations, prosecutions, examinations in court in corruption cases take precedence over other cases for prompt settlement. This study aims to determine the application of material criminal law to the crime of livestock budget corruption in the case of decision Number 1/Pid.Pra/2019.Pn.Lsm, and to find out how the judge's considerations in making a decision on the crime of corruption in the livestock budget in decision Number 1/ Pid.Pre/2019.Pn.Lsm. This study uses a descriptive normative legal research method. Sources of primary and secondary legal materials, data collection techniques are library research, while the analysis of legal materials used in this study is qualitative analysis. Based on the results of the study, it is known that the application of material criminal law to perpetrators of corruption in the livestock budget in the case of decision number 1/Pid.Pra/2019.Pn.Lsm is that in its development, pretrial arrangements are regulated in Article 1 number 10 Jo. Article 77 of the Criminal Procedure Code, there is often treatment of law enforcement officials who are not really serious in reaching the material truth so that the person concerned does not get real legal protection from the state. For that obtain real legal protection from the state. For this reason, such developments can be accommodated through whether or not the determination of suspects is legal and whether the seizure is legal or not, it has been recognized as being the area of pretrial authority, so as to minimize arbitrary treatment by law enforcement officers. It is recommended that law enforcement officers, whether prosecutors, lawyers and judges, must have good knowledge of legal science, especially regarding the criminal law of corruption. If his actions are based on the proper application of criminal law from law enforcement, a sense of justice can be felt for all people.